Analysis of 236U and plutonium isotopes, 239,240Pu, on the 1 MV AMS system at the Centro Nacional de Aceleradores, as a potential tool in oceanography - Chamizo, Elena; López-Lora, Mercedes; Villa-Alfageme, María; Casacuberta, Nuria; López-Gutiérrez, J. M.; Pham, M. K. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2015)
The performance of the 1 MV AMS system at the CNA (Centro Nacional de Aceleradores, Seville, Spain) for 236U and 239,240Pu measurements has been extensively investigated. A very promising 236U/238U abundance sensitivity of about 3 × 10-11 has been recently achieved, and background figures for 239Pu of about 106 atoms were reported in the past. These promising results lead to the use of conventional low energy AMS systems for the analysis of 236U and 239Pu and its further application in environmental studies. First 236U results obtained on our AMS system for marine samples (sediments and water) are presented here. Results of two new IAEA reference materials (IAEA-410 and IAEA-412, marine sediments from Pacific Ocean) are reported. The obtained 236U/239Pu atom ratios, of 0.12 and 0.022, respectively, show a dependency with the contamination source (i.e. local fallout from the US tests performed at the Bikini Atoll and general fallout). The results obtained for a third IAEA reference material (IAEA-381, seawater from the Irish Sea), are also presented. In the following, the uranium and plutonium isotopic compositions obtained on a set of 5 intercomparison seawater samples from the Arctic Ocean provided by the ETH Zürich are discussed. By comparing them with the obtained results on the 600 kV AMS facility Tandy at the ETH Zürich, we demonstrate the solidity of the CNA technique for 236U/238U determinations at, at least, 7 × 10-10 level. Finally, these results are discussed in their environmental context. This work has been financed through the projects FIS2012-31853 provided by the Spanish Ministry of Economy and Competitiveness, and P-10-FQM-5956, provided by the Andalusian Government (Junta de Andalucia, Spain). Peer Reviewed